История России в рассказах для детей - Ишимова Александра Осиповна (Эксмо, 2015)
Экземпляры: ДБ (20150921) / Инвентарный номер: 47397 / Цена: 181.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: И 97 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1